Influence of Thickness on the Holographic Parameters of H-PDLC Materials. (14th December 2014) - Gallego, S.; Ortuño, M.; Márquez, A.; Fernández, R.; Álvarez, M. L.; Beléndez, A.; Pascual, I.
Abstract : For photopolymers the compound concentrations and final thickness of the sample should be known in order to model hologram formation and introduce the reaction-diffusion kinetics of the monomer-polymer system. In principle the cell thickness can be controlled by bead spacers between the two pieces of ITO glass. In this paper we report a study of the influence of thickness on the holographic properties of this type of materials. To fit the physical and optical thickness of the samples we used the rigorous coupled wave analysis assuming an exponential decay in the refractive index modulation.